EFFECT OF CULTURE ON LANGUAGE USED IN COMMUNICATION TECHNOLOGY BY UNIVERSITY STUDENTS - MMBWANGA, FLORENCE; SIMIYU, EVERLYN (Machakos University, 2018)
Communication technology exists to connect, inform, entertain and marketing. Developments in communication technology force people to think differently about how they disclose information.Atelephone call or a few clicks make any kind of message worldwide news. This results from the fact that with cell phones, tablets and laptops,communication has become extremely portable and even intrusive into people’s daily lives since everybody can communicate at almost any time and from anywhere. The most commonly used type of communication technology is radio, television and the internet. This offers both positive developments and downsides. A people’s culture impacts greatly on the language used in communication technology .Males and females differ in the way they speak, reason, feel and act. This is also notable in the topics theyshare,what they wish to achieve by making posts and how they communicate. This study focuses on how culture affects the language used in communication technology.Identify the most commonly used forms of communication technology. The study used both qualitative and quantitative approach.The objectives of this study were designed to answer the questions of whether culture changes language used in communication technology, how different cultures affect the language used in communication technology. The different cultures and their varied effects on the language used in communication technology by the university students. Purposive sampling will be used to get the respondents.Qualitative and quantitativemethods were used to analyze thedata. The Uses and Gratification Theory byBlumler and Katzwas used to inform this study.The findings of the study will be used to create awareness and encourage society to embrace the dynamism in language and be able to communicate adequately in varied situations
Keywords: Culture